2013
DOI: 10.2196/jmir.2929
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Text Message Program to Raise Type 2 Diabetes Risk Awareness and Promote Health Behavior Change (Part II): Assessment of Participants' Perceptions on Efficacy

Abstract: BackgroundAlthough there is great enthusiasm in both the public and private sector for the further development and use of large-scale consumer-facing public health applications for mobile platforms, little is known about user experience and satisfaction with this type of approach. As a part of the Beacon Community Cooperative Agreement Program, txt4health, a public-facing, mobile phone-based health information service targeting type 2 diabetes, was launched in 3 Beacon Communities: the Southeast Michigan Beaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 10 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…These findings were similar to other research finding, that texting was easily accepted by subjects. 24 SMS was found to affect the promotion of health awareness, 25 health knowledge, [26][27][28] and changing unhealthy behavior or improving therapy. [29][30][31][32][33][34] SMS was more effective than pamphlets in improving knowledge, attitude, and practices, especially in promoting physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were similar to other research finding, that texting was easily accepted by subjects. 24 SMS was found to affect the promotion of health awareness, 25 health knowledge, [26][27][28] and changing unhealthy behavior or improving therapy. [29][30][31][32][33][34] SMS was more effective than pamphlets in improving knowledge, attitude, and practices, especially in promoting physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…23 Consumer e-health tools-electronic tools and services, including secure messaging between patients and providers, mobile health (mHealth) apps, and existing technologies used in novel ways-offer unique opportunities to improve patient-provider communication and facilitate patient engagement. [24][25][26] A growing body of evidence suggests that patient use of new technologies such as text messaging [27][28][29][30] or email 31 to communicate with healthcare providers can lead to behavior change and improved health outcomes for select patient populations. Novel digital technology tools for engaging a wider group of patients are rapidly emerging.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with long-duration diabetes are less interested and motivated to maintain self-care actions, to adhere to pharmacological treatment, or to implement changes in their lifestyles compared to recently diagnosed patients. 21 Other outcomes, such as quality of life and patient satisfaction, also show the efficacy of telephone-based educational interventions. One study conducted in the United States in 2013 adopted the RE-AIM model to assess the efficacy of a health information service provided via mobile phone.…”
Section: Dimentions Of the Re-aim Model From The Perspective Of Telepmentioning
confidence: 99%
“…The study shows that health information provided via mobile phone was positive and promoted positive behavioral changes, especially in terms of eating habits and exercises. 21 One observational study conducted in the interior of São Paulo, Brazil, assessed the expectations and satisfaction of patients who received telephone-based diabetes follow-up and showed that 77.8% of the patients were satisfied with the information provided. 12 Assessing the efficacy of telephone-based educational interventions may represent advancement for health services.…”
Section: Dimentions Of the Re-aim Model From The Perspective Of Telepmentioning
confidence: 99%